The effect of the dynamics of knowledge base complexity on Schumpeterian patterns of innovation: the upstream petroleum industry. (15th November 2016) - Maleki, Ali; Rosiello, Alessandro; Wield, David
Abstract : This article analyzes important changes in technological innovation in the upstream petroleum industry. It provides evidence that shifts in sectoral patterns of innovation over the petroleum industry's lifecycle from the 1970s up to 2005 were dependent on the dynamics of knowledge base complexity (KBC), a key dimension of an industry's technological regime. Accordingly, observed shifts in innovation patterns are understood to be the aggregated strategic response of industry innovators to changes in the technological regime. The article proposes a quantitative method for exploring KBC and Schumpeterian patterns of innovation, and interactions between the two at the industry level. As the industry evolved, its knowledge base moved to higher orders of complexity creating a shift in the Schumpeterian pattern of innovation. Increased KBC was found to alter Schumpeterian patterns from Mark I toward a 'modified' Mark II. Instead of coming predominantly from 'traditional' established oil operators, technological innovation was increasingly triggered by a new class of emergent integrated service companies – 'second tier' systems integrators of the upstream sector able to cope with increased KBC.